2007
DOI: 10.1038/bdj.2007.584
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of the lingual nerve to the third molar region using radiographic imaging

Abstract: PRACTICE I N B R I E F• Lingual nerve damage is a common complication during oral and maxillofacial surgery procedures in the third molar region.• The anatomy of the lingual nerve is variable; therefore precise anatomical knowledge of this nerve is important for decreasing the damage risk.• The data presented in this paper should be a useful reference for surgical procedures undertaken by maxillofacial surgeons.The relationship of the lingual nerve to the third molar region using radiographic imaging P. Karaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Dias et al [4] noted that the horizontal distance of the lingual nerve from the third molar bone crest was 0.57–9.30 mm, and that the nearest distance was 0 mm [4-6]. The vertical distance of the lingual nerve from the third molar bone crest was 2.28–16.8 mm, and the nearest distance was 1.13 mm [7-9]. Another study reported a lingual nerve running onto an alveolar crest and warned of the possibility of damage to the lingual nerve in third molar extraction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dias et al [4] noted that the horizontal distance of the lingual nerve from the third molar bone crest was 0.57–9.30 mm, and that the nearest distance was 0 mm [4-6]. The vertical distance of the lingual nerve from the third molar bone crest was 2.28–16.8 mm, and the nearest distance was 1.13 mm [7-9]. Another study reported a lingual nerve running onto an alveolar crest and warned of the possibility of damage to the lingual nerve in third molar extraction [10].…”
Section: Introductionmentioning
confidence: 99%
“…[18]. The similarity of the data from studies by Karakas et al [2] and Erdogmus et al [7] which were from same population shows that probably ethnicity has a major influence on the LN dimensions. Previous studies have not correlated LN parameters with the mandibular height.…”
Section: Discussionmentioning
confidence: 66%
“…Karakas et al [2] reported a mean vertical distance of 9.51 mm which differed from a study by Miloro et al [3] who found a mean of 2.75 mm in which using magnetic resonance imaging to visualize the nerve. Ethnicity may be a major factor leading to this difference since the data were obtained from different populations.…”
Section: Introductionmentioning
confidence: 67%
“…It is a thick nerve whose mean diameter is 2.56 mm (Karakas et al, 2007), and runs the infratemporal region and descends in search of the submandibular hiatus, through which it penetrates the paralingual space where it emits its terminal rami; at the height of the lower second molar, the lingual nerve makes a medial curve to surround the submandibular conduct and emit its terminal rami (Chan et al, 2010a). In its course, the lingual nerve can establish communications with the mylohyoid nerve, which completes its innervation and explains a percentage of aneasthetic failures (Behnia et al, 2000;Kim et al, 2004).…”
Section: Irrigation and Drainagementioning
confidence: 99%